The concept of “resembling unification” in John of the Cross’ mysticism - Bańka, Aleksander R. (Folia Philosophica, 2010)
The idea of „resembling unification” as developed by John of the Cross is broadly discussed by scholars of his work. The key queries here are not only those of how this kind of unification, the highest moment of mystical unification possible in earthly life, is possible in the mystic’s soul, but also what role is played by two fundamental powers of soul: mind and will. In John’s view their tasks are clear: while unifying with God they turn towards their supernatural objects, which are the virtues of, respectively, faith and love. Yet, the problem of what is the nature of the unification thus understood remains unsolved. Is it a kind of intellectual insight or an experience of emotion and will? How should be understood the „substantial touches” in the very heart of the soul which John mentions in the descriptions of states of the highest unification? Finally, what is the difference between unification in the substance of the soul and transformation of its powers and is this unification identical with participation in the life of God itself as John describes it? The aim of the paper is to answer those questions.